Study on the mechanism and control of ground subsidence induced by solution mining in Guangzhou Longgui Nitrate-Salt Mine - Chen, Jian; Liu, Xuchao; Liu, Jinsen; Wang, Pan (Frontiers in Materials, 2025)
Solution mining is widely applied in underground salt rock extraction, but it is prone to inducing ground subsidence. Under complex geological conditions, its mechanism is more complicated, posing a significant threat to engineering safety and the ecological environment. The Guangzhou Longgui Nitrate-Salt Mine, due to the direct contact between salt-bearing strata and highly permeable argillaceous conglomerate layers, has seen continuous development of ground subsidence with an accelerating rate caused by long-term solution mining. To clarify the subsidence mechanism and predict future trends, the geological structure, aquifer distribution, and cavity development characteristics of the mining area were analyzed through on-site investigations and geophysical methods (Controlled Source Audio-Frequency Magnetotellurics). The causes of subsidence were systematically explored, and a numerical simulation model was established based on mining data and monitoring results to invert historical subsidence patterns and predict future trends. It was found that the core mechanism of accelerated subsidence is the collapse of upper pillar groups triggered by pillar dissolution, and this process is further exacerbated by the hydraulic connection between adjacent cavities and permeable aquifers. Numerical predictions show that subsidence will continue to intensify. By 2050, the maximum subsidence in Mining Area I will reach 1,553 mm (with a rate of 12.05 mm/year), and that in Mining Area II will reach 2096 mm (with a rate of 44.78 mm/year). After well sealing, cavity group creep and compaction of insoluble residues will gradually slow down the subsidence rate.This study innovatively reveals the coupled mechanism of ground subsidence under the interaction between complex geological conditions and solution mining, providing accurate prediction data and technical support for subsidence prevention and control in Longgui and similar mining areas. It emphasizes the necessity of strengthening monitoring and implementing targeted emergency measures to reduce disaster risks.